Basic Package for Oral Care: A Means to Tackle Community Dental Needs - Dharmashree Satyarup1, Manish Kumar2, Radha Prasanna Dalai3, Karishma R. Rathor4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
There exists a gaping rift between the available dental services and the need for dental care in communities,giving rise to the ‘inverse care law’. WHO in collaboration with the University of Nijmegen, worked alongthe principles of Primary Health Care (PHC) to give the Basic Package of Oral Care (BPOC) which isdesigned to cater to the dental needs of outreach populations within the confines of minimum resourcessuch as lack of electricity and dental setup, for a maximum effect of providing emergency, preventive andcurative dental care. Implementing BPOC with prudent use of existing PHC workforce, local resources andcollaboration with NGOs could be the best answer to tackling the dental needs of communities.